Paradigma pemahaman dan klasifikasi Sunnah dalam perpektif edukatif Mahmud Syaltut dan implikasinya terhadap aktualisasi mekanisme ra’yu era kekinian - Fatih, Muhammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
The effort to understand Sunnah by linking the function of Prophet Muhammad has done many times by a number of ulama, and one of them is Mahmud Syaltut, who classified Sunnah into sunnah tasyri' dan sunnah ghairu tasyri'. Even he is the first person who uses such a term, and devides sunnah tasyri' into tasyri' ’amm dan tasyri' khas. Sunnah tasyri’ is a sunnah which is the consequence of syariah law which tie and should be done by all moslems in every period, place, and situation. Whereas sunnah ghairu tasyri’ is sunnah which is not the consequence of syariah law which does not tie, so that the implementation can be matched with the situation and concition where such a sunnah is implemented. Included to sunnah ghairu tasyri’ is sunnah in context of human management in anticipating certain condition, like the division of group to be placed in battle posts, managing the rank in a battle, in military shelter barrack, the stride to attack or retreat, choosing the place and stategy for the defense, and another policy based on certain situation and condition. Those factors are not the matter of syariah which has relationship to be done or left yet the matter of usual human. The attitude and action of Messenger for those matters are not believed as the law or the source of the law. While sunnah as tasyri' ’amm is all sunnah which is from the prophet in form of tabligh in his capacity as Messenger. For example, explaining the verse which is global, specifying general wording, limiting absolute wording, explaining the matters about worship, lawful, unlawful, and moral, or cases related to those matters. All of them is universal sunnah tasyri’ until the hereafter. If the law is in form of prohibition, so automatically all people should keep away from it. It is impossible for someone to understand it without deep knowledge. While sunnah as tasyri' khass included sunnah which is from the Prophet as statesman and leader of moslems. For example, sending the troops at war, using the property of baitul mal well, collecting the property of baitul mal from certain sources, inaugurating the judges and officials, sharing the spoils of war, making treaty, etc which is included the duty of statesman and generral management for the benefit of citizens